The Economic Upside of Green Real Estate Investments: Analyzing the Impact of Energy Efficiency on Building Valuation in the Residential Sector - Timo Deller (Junior Management Science (JUMS), 2022)
The rising sustainability awareness will affect the carbon-intensive European real estate industry and will force it to adapt to meet climate targets. The purpose of this thesis is to examine whether the energy efficiency of buildings plays a role in the valuation of buildings in the residential sector in the Rhein-Main Region in Germany. This is done by looking at the impact of energy performance certificates of buildings on their rent and sales prices. Data from publicly available real estate advertisements for the years 2019-2020 are analyzed using hedonic regression models. The rent market analysis (N = 44 442) finds significant cold rent premiums of 5.82%, 2.04%, 3.06% for A+, A and B rated buildings compared to the reference level of D. Significant warm rent premiums of 3.86% and 1.98% are found for A+ and B rated buildings. No significant discounts are found for buildings rated below D for cold and warm rents. The sales market analysis (N = 31 426) shows significant premiums of 6.81%, 3.14% and 1.52% for A+, A and B rated buildings, a range of indifference with no premiums or discounts for C to F rated buildings and discounts of -1.73% and -8.80% for G and H rated buildings. The results show that high energy efficiency of buildings creates significant value for investors.
Keywords: 650; Real estate investments; real estate valuation; green buildings; energy efficiency; sustainability